Factors Affecting Uterine Prolapse among Females of 20-35 years on Semi-urban Area of Kathmandu District - Panta, Prem Prasad; Phuyal, S.; Sharma, D.; Amgain, K. (Journal of Karnali Academy of Health Sciences, 2018)
Uterine prolapse is a significant public health problem in Nepal. The aim of this study was to determine the prevalence of uterine prolapse and to identify the possible risk factors for this. This is a cross sectional study conducted at semi urban area in Kathmadu district. A total of 168 women of age 25 – 34 years were surveyed, and nearly half of them were of 25-29 years. Maximum respondents (38.1%) were Chhettri, and least was Dalit (13.1%). Regarding occupation, two –third of the participants had agriculture and house maker as their main source of living. Among the interviewed population, the prevalence of uterine prolapse was found to be 11.9%. Among them, 15.3% were farmers, 29.4 % were daily wagers, 18.2% were Dalit and 16.7% were of age more than 28 years. This study showed that the income has a vital role in the occurrence of the uterine prolapse, the odds ratio was found to be 13.6 (CI: 4.6-38.5). The pregnancy below the age of 20 was found to be the second major cause (OR: 12.6, CI: 3.5 - 45). Similarly, other factors like parity, gravid, child spacing, lack of rest during pregnancy, heavy weight lifting were the significant factors to uterine prolapse (p